Spectral, Magnetic and Biological Studies of ZnII Complexes of Schiff Bases Derived From 4-(O-Methoxyphenyl)-2-Aminothiazole - Netaji N. Karale, Rajendra H. Patil (Journal of Applied Pharmaceutical Science, 2015)
In the present ZnII complexes of Schiff bases (SB-1 to SB-7) derived form 4-(o-methoxyphenyl)-2-aminothiazole and R substituted salicylaldehyde (R = H, 3-Me, 4-Me, 5-Me, 3-OMe and 5-Br) and 2-hydroxy-1-naphthaldehyde o-hydroxyaldehydes were synthesized, characterized and tested for the bioactivity against Gram positive and Gram negative group of organisms. The as-synthesized complexes were characterized by elemental, spectral and spectroscopic methods for measuring magnetic susceptibility, conductivity and assayed for biological activities. The complexes showed 1:2 metal : ligand stoichiometry (ML2) and an octahedral geometry. The complexes showed an antibacterial activity against Bacillus subtilis 2063 and Escherichia coli 2931, and antifungal activity by preventing the dimorphic switching in Candida albicans.
Keywords: ZnII complexes, Schiff base, dimorphic switching, antibacterial activity.